Subclinical Atherosclerosis in Young Adult Population with First Degree Relatives of Type 2 Diabetes Mellitus - Abdaly, Muhammad Syah; Azizi, Mohamad Syahrir; Wijaya, Ika Prasetya; Nugroho, Pringgodigdo; Purnamasari, Dyah (Acta Medica Indonesiana, 2019)
Cardiovascular disease (CVD) remain a leading cause of death globally. The concept of acute myocardial infarction in young adults was uncommon. Atherosclerosis is the leading cause of CVD, including myocardial infarction, stroke, heart failure and peripheral artery disease. This condition is initiated early in childhood and progressive in nature. CVD risk factors includes hypertension, dyslipidemia and obesity play a role in the development of atherosclerosis and components in insulin resistance syndrome. One of many risk factors for insulin resistance in healthy individuals is a first-degree relative (FDR) of Type 2 Diabetes Mellitus (T2DM) patients. This group shows a higher risk of insulin resistance and pancreatic beta cells disruption even in adolescence, although they often remains asymptomatic. Clinical manifestations of metabolic disorders and atherosclerosis will appear earlier in the FDR T2DM group who have sedentary lifestyles and obesity, when compared to the non-FDR group. Several studies have attempted to detect metabolic disorders and subclinical atherosclerosis that might occur; therefore an early prevention can be carried out in these high-risk groups. Unfortunately, factors that affect the onset and the severity of the prospective clinical manifestations from the previous studies remained inconclusive.